AZIMUTHAL FLOWS IN THE EARTH'S CORE AND CHANGES IN LENGTH OF DAY AT MILLENNIAL TIMESCALES - Dumberry M.; Bloxham J. (My University, 2006)
Variations in the length of day (LOD) reconstructed from ancient records of eclipses contain an oscillating component with a periodicity of roughly 1500 yr. A part of the time-dependent variations observed in archaeomagnetic field models consist of episodic eastward and westward motions with a similar periodicity. Using standard inversion techniques, we obtain time-dependent azimuthal flows at the surface of the core that can explain parts of the archaeomagnetic secular variation, and with amplitude and characteristic timescale of variation consistent to explain the LOD signal. On this basis, we argue that exchanges of angular momentum between core flows and the mantle are responsible for the observed millennial oscillations in the Earth's rotation rate. However, we do not obtain a detailed match between the observed changes in LOD and the prediction based on simple flow profiles inside the core. We argue that this is due to the presence of time-dependent azimuthal flows that have an important shear in the direction of the rotation axis. Such flows are interpreted as oscillations in thermal and magnetic winds. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CORE DYNAMICS; CORE-MANTLE COUPLING; EARTH'S MAGNETIC FIELD; EARTH'S ROTATION; GEOMAGNETIC VARIATION; LENGTH OF DAY